Multi-criteria Assessment Using AHP Techniques for Agricultural Land Suitability Sharazoor and Sharbazher, Sulaimani as a Case study - Ahmed, Sivan Bakr; Hama, Ako Rashed; Ziboon, Abdul Razzak T. (Sulaimani Journal for Engineering Sciences, 2023)
Land suitableness evaluation should be essential before implementing any specific land use, particularly within the agricultural sector. The aim of this study was to determine suitable lands for agricultural use in the Sharazoor and Sharbazher districts. The Analytical Hierarchy Process method, commonly used in land-use suitability analysis, was used in this study. According to Analytical hierarchy process (AHP) techniques, to generate a land suitability graph various main criteria such as climate (rain, temperature, humidity), soil (texture, colour, PH ), land (elevation, slope, area, distance), and Agriculture services (Crop rotation, pesticide type, planting scheduling date, Seed variety, farm management, education level, number of personal work in the farm, equipment, production rate, planting rate, planting days, harvesting) factors were used. The questionary form is created. The form was distributed to academic people and ideal farmer for determine the importance of each criterion. In the result, the weight value is 0.465, 0.242, 0.209, and 0.084 for the Climate, Soil, Land, and Agriculture service respectively. Climate criteria are most important, and Agriculture has the least influence over decision-making procedures. According to AHP techniques, the ranking value ranges between 6.48-5.06 for producing wheat in the study area. The suitable land for producing wheat is in Kanispika village. Kelakawa Village's land is best suited for producing barely, when ranking values ranging from 6.08 to 5.15.
Keywords: separately excited DC motor (SEDCM); water pump; field weakening